Case Report: Effects of Secondary Hyperparathyroidism Treatment on Improvement of Juvenile Nephronophthisis-Induced Pancytopenia and Myelofibrosis - Amano, Keishiro; Toyoda, Hidemi; Nishikawa, Kouhei; Murata, Tomohiro; Hirayama, Masahiro (Frontiers in Pediatrics, 2021)
Secondary hyperparathyroidism (HPT) is a common complication of end-stage renal disease (ESRD) and may be an important precipitating factor for the development of myeloﬁbrosis. However, there have been only a few reports on myeloﬁbrosis caused by secondary HPT in children. We describe a case of a 15-year-old boy with myelofibrosis due to secondary HPT who was successfully treated with hemodialysis, erythropoietin, phosphate binders, and activated vitamin D agents. The patient had no past medical history and had been admitted to the hospital for abdominal pain. Routine blood examination revealed pancytopenia combined with renal impairment. Hyperphosphatemia, decreased 1,25-dehydroxyvitamin D, decreased serum calcium, and increased parathyroid hormone (PTH) levels were observed. Bone marrow biopsy confirmed myelofibrosis and renal biopsy revealed nephronophthisis (NPHP). The possibility of renal osteodystrophy and myelofibrosis due to secondary HPT was considered. Hemodialysis and erythropoietin were initiated and combined therapy with a phosphate binder and an active vitamin D agent achieved greater reduction of PTH levels, along with improvement of pancytopenia. As medical treatment for secondary HPT can lead to a reversal of myelofibrosis and avoid parathyroidectomy in children, prompt recognition of this condition has major implications for treatment. Therefore, despite its rarity, pediatricians should consider myeloﬁbrosis due to secondary HPT as a cause of pancytopenia in patients with chronic kidney disease.